Teorijska promišljanja kulture i umjetnosti kao postmodernistička / Theoretical Rethinking of Culture and Arts in Postmodernist Terms - Jašarević, Merima (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
The arts and culture developed by rejecting, criticizing or correcting the modern arts and culture is called postmodern. The 20 th century‟s art history can be divided in two “sides” – abstract art at one side and ready-made (via dada, surrealism, fluxus, neo-dada, pop art, minimalism and conceptual arts) at the other. To work with value or meaning of an artwork it implies taking two directions – relativist (treat it through the prism of cultural context) or realistic (how exterior necessity creates the subject and arts). The loss of all criteria, eclecticism as a pivot of contemporary culture: reggae music and a world-renowned fast food brand - McDonald's; killing the illusion of the world in favor of absolutely real world is in the true sense of the word simulation. For the very purpose of art, it is better for it to be elitist - subversive, provocative and to operate in the field of expertise. The art-culture relationship is very important, which unfortunately for our area, the former Yugoslav countries, is not so. The 20th century artists draw inspiration precisely from the nature of human existence - the search for self, by building a new world that in a very meaningful way narrates of reality.